PENGGUNAAN HAND SANITIZER TERHADAP KEPATUHAN REMAJA MENCUCI TANGAN DI KELURAHAN LUBUK PAKAM PEKAN - Pitri Ani; Juni Mariati Simarmata; Samuel Ginting; Syatria Wati; Efpik Fantanti Jawak; Luci Riani Ginting (JURNAL PENGMAS KESTRA (JPK), 2021)
Hand washing is a process that mechanically removes dirt and debris from the skin of the hands using plain soap and water. The purpose of this community service is to use hand sanitizers for adolescent compliance with washing hands in the Lubuk Pakam Village, Weekend. The community service method uses this form of pre-experimental research carried out with a one-group pretest-posttest design in which there is a pretest (before treatment). The population of this community service is 41 teenagers with a sampling technique using total sampling. The results of community service for hand washing compliance before using hand sanitizers obtained the number of "obedient" as many as 8 people (19.5%), compared to 30 (73.2%). -test obtained p-value = 0.000 < a = 0.05, then the hypothesis is accepted, so it can be concluded that there is the use of hand sanitizers on hand washing compliance in Lubuk Pakam weekend. Conclusion: teenagers want to wash their hands using hand sanitizer after direct contact with strangers to prevent cross infection with the covid 19 virus.